2021
DOI: 10.1177/00027642211021633
|View full text |Cite
|
Sign up to set email alerts
|

Protest as One Political Act in Individuals’ Participation Repertoires: Latent Class Analysis and Political Participant Types

Abstract: This study advances research on the role of protest in individual-level participation repertoires by examining how latent class analysis can be used to identify distinctive types of political participants. This methodological approach requires shifting researchers’ traditional theoretical and analytical focus on protest as a single political act to the ways in which political actors combine protest with other political behaviors. From a theoretical perspective, the study examines the increased salience of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Capturing political repertoires (i.e., how citizens choose to engage with the various available modes of political action), allows researchers to grasp the state of participatory democracy in a more accurate manner. And thus, by incorporating various participatory modes into research designs, a biased literature can be avoided [4,54].…”
Section: Young People's Political Participation and Repertoiresmentioning
confidence: 99%
See 4 more Smart Citations
“…Capturing political repertoires (i.e., how citizens choose to engage with the various available modes of political action), allows researchers to grasp the state of participatory democracy in a more accurate manner. And thus, by incorporating various participatory modes into research designs, a biased literature can be avoided [4,54].…”
Section: Young People's Political Participation and Repertoiresmentioning
confidence: 99%
“…Most studies using a repertoire-based approach, have shown how different forms of political action tend to coexist, rather than cannibalize one another. It seems that participation patterns are becoming increasingly hybrid and individualized as they combine different types of participation [4,17,18]. In a study addressing a Belgian climate movement, De Moor, Marien & Hooghe [24] found that forms of lifestyle politics often exist within complex political repertoires that also include state-oriented forms of action.…”
Section: Young People's Political Participation and Repertoiresmentioning
confidence: 99%
See 3 more Smart Citations